French lyophilized plasma versus fresh frozen plasma for the initial management of trauma‐induced coagulopathy: a randomized open‐label trial. (22nd January 2018) - Garrigue, D.; Godier, A.; Glacet, A.; Labreuche, J.; Kipnis, E.; Paris, C.; Duhamel, A.; Resch, E.; Bauters, A.; Machuron, F.; Renom, P.; Goldstein, P.; et al.
Abstract : Essentials An immediate supply of plasma in case of trauma‐induced coagulopathy is required. The Traucc trial compared French Lyophilised Plasma (FLyP) and Fresh Frozen Plasma (FFP). FLyP achieved higher fibrinogen concentrations compared with FFP. FLyP led to a more rapid coagulopathy improvement than FFP. Summary: Background: Guidelines recommend beginning hemostatic resuscitation immediately in trauma patients. We aimed to investigate if French lyophilized plasma (FLyP) was more effective than fresh frozen plasma (FFP) for the initial management of trauma‐induced coagulopathy. Methods: In an open‐label, phase 3, randomized trial (NCT02750150), we enrolled adult trauma patients requiring an emergency pack of 4 plasma units within 6 h of injury. We randomly assigned patients to receive 4‐FLyP units or 4‐FFP units. The primary endpoint was fibrinogen concentration at 45 min after randomization. Secondary outcomes included time to transfusion, changes in hemostatic parameters at different time‐points, blood product requirements and 30‐day in‐hospital mortality. Results: Forty‐eight patients were randomized (FLyP, n  = 24; FFP, n  = 24). FLyP reduced the time from randomization to transfusion of first plasma unit compared with FFP (median[IQR], 14[5–30] vs. 77[64–90] min). FLyP achieved a higher fibrinogen concentration 45 min after randomization compared with FFP (baseline‐adjusted mean difference, 0.29 g L −1 ; 95% confidence interval [CI], 0.08–0.49) and a greater improvement in prothrombin time ratio, factor V and factor II. The between‐group differences in coagulation parameters remained significant at 6 h. FLyP reduced fibrinogen concentrate requirements. Thirty‐day in‐hospital mortality rate was 22% with FLyP and 29% with FFP. Conclusion: FLyP led to a more rapid, pronounced and extended increase in fibrinogen concentrations and coagulopathy improvement compared with FFP in the initial management of trauma patients. FLyP represents an attractive option for trauma management, especially when facing logistical issues such as combat casualties or mass casualties related to terror attacks or disasters.